Kaivalyadīpikā = Kaivalyadīpikā : (with Prabhā commentary) - Kr̥ṣṇapaṇḍita ca. activ im 18. Jahrhundert (Śrīsomanāthasaṃskṛtaviśvavidyālayasaṃśodhanagranthamālā, 2018)
Sanskrit text with commentary on Advaita philosophy by Kr̥ṣṇapaṇdita, 18th century: based on rare manuscripts